An Isolated Midsubstance ACL Tear Repaired With the BEAR System - Patrick F. Szukics DO; Brian E. Fliegel DO; William F. Baker DO; Hannah Popper DO; Sean McMillan DO (Video Journal of Sports Medicine)
Background: Anterior cruciate ligament (ACL) repairs, once widely abandoned due to historically high failure rates, have recently regained interest with the development of the bridge-enhanced ACL repair (BEAR) implant, a novel arthroscopic technique that uses a resorbable protein-based implant combined with autologous blood to primarily repair a midsubstance ACL tear. This technical note presents a step-by-step surgical method for performing an isolated midsubstance ACL repair using the BEAR implant. Indications: The BEAR implant is indicated for skeletally mature patients at least 14 years of age with a complete rupture of the ACL, confirmed by magnetic resonance imaging. The complete ACL tear must have an attached stump to the tibia. Technique Description: A diagnostic arthroscopy is used to confirm complete rupture of the ACL and presence of residual tibial stump. A self-retrieving suture passage device is used to whipstitch a total of 6 passes with #2 Vicryl suture from distal to proximal through the residual stump. A notchplasty followed by femoral and tibial tunnels is created in a standard fashion. An Endobutton, soaked in a bacitracin solution, is then loaded with the sutures that were previously passed through the residual ACL stump and then through the femoral tunnel and cinched down to bone. The 4 suture ends that are coming from the Endobutton are then passed through the BEAR implant with the use of a Keith needle and shuttled through the tibial tunnel. The BEAR implant is hydrated with 15 cc of the patient's blood and is shuttled through the anteromedial portal with the knee in full extension. The 4 tibial sutures passed through the graft and tibial tunnel are passed, and tensioned to the proximal tibial with a second Endobutton. Standard closure and dressings are applied. Results: This new surgical implant and technique have shown noninferiority to ACL autograft reconstruction with respect to the International Knee Documentation Committee and anteroposterior laxity, with improved hamstring strength and decreased incidence of contralateral ACL tears at 2 years postoperative. Discussion/Conclusion: While initial data remain promising, future long-term designed studies are needed to determine the clinical efficacy of the BEAR technique, particularly comparing itself with bone-patellar tendon-bone autograft ACL reconstruction. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.